Evaluation Of Mandiri Cash Management 2.0 Services Usage - Maria Sylvia Agustin Dwi Afrianti*; Tanti Handriana (Universitas Syiah Kuala, 2023)
Digitalization in the current era is the main focus for all fields, especially the banking world. Offering technology-based services and products and starting to abandon conventional systems. Digital banking financial services have become one of the main focuses of the banking world. With the Mandiri Cash Management 2.0 service, Bank Mandiri makes it easy for wholesale segment customers to get this convenience. However, as time passed, the MCM 2.0 service, which was expected to provide convenience, gave rise to several issues, especially regarding the technology service. This issue makes customers return to conventional transactions when the problem has not been completely resolved. This service must, of course, pay attention to digital quality network connections and human resources to support it.